2021
DOI: 10.1088/1741-4326/ac2b75
|View full text |Cite
|
Sign up to set email alerts
|

Plasma radiation behavior approaching high-radiation scenarios in W7-X

Abstract: The W7-X stellarator has so far performed experiments under both limiter and divertor conditions. The plasma is mostly generated by ECR-heating with powers up to 6.5 MW, and the plasma density is usually limited by the radiation losses from low-Z impurities (such as carbon and oxygen) released mainly from the graphite targets. The present work first summarizes the radiation loss fractions f rad achieved in quasi-stationary hydrogen plasmas in both operational phases, and then shows how impuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…The dashed vertical lines mark the selected time points for performing bolometer tomography. reduction of impurity radiation from the core at medium f rad is also observed in discharges conducted after wall boronization, which have a lower Z eff value, usually below 1.5 [55]. We believe that the evident core impurity radiation in figures 10(a) and (d) is related to the weak screening effects of the magnetic islands on both impurities and neutral hydrogen at the low edge densities of 0.6-0.8 × 10 19 m −3 (see figure 8) [28].…”
Section: Tomographic Reconstructionsmentioning
confidence: 78%
“…The dashed vertical lines mark the selected time points for performing bolometer tomography. reduction of impurity radiation from the core at medium f rad is also observed in discharges conducted after wall boronization, which have a lower Z eff value, usually below 1.5 [55]. We believe that the evident core impurity radiation in figures 10(a) and (d) is related to the weak screening effects of the magnetic islands on both impurities and neutral hydrogen at the low edge densities of 0.6-0.8 × 10 19 m −3 (see figure 8) [28].…”
Section: Tomographic Reconstructionsmentioning
confidence: 78%
“…The energy transfer between the electrons and ions Q e-i is a sink for the electrons and a source for the ions, and the power density profile p e-i is calculated from the kinetic profiles using equation (2.1). The radiated heat flux Q rad is the volume-integrated power density profile p rad obtained from a poloidal integration of the tomographic reconstruction of the bolometer multiple lines of sight [47,48]. Finally, a sink for the ions is the charge exchange loss Q cx between the hot ions and cold neutrals entering the plasma.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The ECRH heat deposition profile is calculated from the launch geometry using VMEC for equilibrium and the TRAVIS code for ray tracing [39]. The radiation loss profile is estimated from bolometer inversion profiles and is located towards the edge of the plasma [47,48], as can be seen in appendix A. The stored energy and normalized pressure of this plasma are W th = 0.5 MJ with a normalized pressure of β ∼ 0.5%, and τ E,exp /τ ISS04 = 0.65.…”
Section: Neoclassical Transport Compared To Experimental Findingsmentioning
confidence: 99%
“…as one of its possible actuators in future experiments. Additional radiation scaling studies for W7-X based directly on bolometer data can be found in [34].…”
Section: Dependency Of the C 2+ Radiation Intensity On The Electron D...mentioning
confidence: 99%